Effect of indolbutyric acid (AIB), pyraclostrobin (F 500) and inoculante biológicoon the rooting and initial growth of mini-cuttings of coffee (Coffea arabica) F1 hybrids. - Sosa Mora, Carolina (2019)
At CATIE, the technique of rooting mini-cuttings is being used for the multiplication of coffee hybrids in a short time and at a low cost. In the continuous search to improve the process, in this work we evaluated the effect of different combinations of AIB, a biological inoculant and Pyraclostrobin (F 500), plus a conventional treatment of nutrients and stimulators, on the rooting of cuttings of three F1 coffee hybrids (L2A30, L4A5, L12A28) and its subsequent development in nursery. The rooting phase lasted for 11 weeks, and at the end of this period, there were no significant differences in the percentage of rooting between treatments or between hybrids, with percentages higher than 80% in all cases. There were no significant differences between treatments for the variables of number, length of roots or weights of aerial part and roots. The L2A30 and L12A28 hybrids were significantly superior to L4A5 in terms of number and length of roots, fresh and dry weight of roots and aerial part. The cuttings were then trasplanted into bags with soil for the nursery phase, for a growth period of 3 months. At the end of this phase, the conventional treatment and the combinations AIB + biological inoculant and AIB + Pyraclostrobin (F 500) were significantly superior in terms of plant height and number of leaves. The L4A5 and L2A30 hybrids were significantly higher than L12A28 in terms of total height and number of leaves, while L2A30 and L12A28 showed a greater basal diameter than L4A5. The multiplication of selected hybrids was achieved on a massive scale and at low cost.